Α, β-Dehydrogenation of esters with free OH and NH functionalities via allyl-palladium catalysis. Issue 26 (28th June 2018) - Szewczyk, Suzanne M.; Zhao, Yizhou; Sakai, Holt A.; Dube, Pascal; Newhouse, Timothy R.
Abstract: A direct and selective method for the α, β-dehydrogenation of esters using palladium catalysis in the presence of free OH and NH functionalities is reported herein. Allyl-palladium catalysis allows for preservation of readily oxidizable functionalities such as amines and alcohols. Furthermore, an economical protocol using LDA was developed for the dehydrogenation of β-amino esters. Graphical abstract: Image 1